Epigenetics in Clinical Practice: Characterizing Patient and Provider Experiences with MTHFR Polymorphisms and Methylfolate. - Oberg, Erica; Givant, Chris; Fisk, Briana; Parikh, Carina; Bradley, Ryan (Journal of Nutrigenetics & Nutrigenomics, 2015)
Background: Observational research associating 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphisms with risk of autism, depression, cancer, and cardiovascular disease has led to increased diagnoses of MTHFR; however, doctors lack knowledge about safety, effectiveness, and clinical implications of MTHFR treatment. Treatment strategies are hypothetical and mechanistically based, including methylfolate with or without other B vitamins.Aims: This study was designed to formally describe patient and health care provider experiences with the diagnosis and clinical management of MTHFR.Methods: Guided by a structured interview guide, a qualitative study queried patients' and providers' observations regarding: testing indications, reaction to results, treatment protocols, and clinical response including adverse effects.Results: Thirty patients and 8 doctors participated. Patient themes included emotionality associated with diagnosis, classification of signs and symptoms, and challenges with treatment. They expressed confusion over their diagnosis, and frustration with the state of knowledge their providers had regarding MTHFR. Testing indications included: fatigue (21%), hormone imbalances (13%), and neurological symptoms (13%) including brain fog (8%). Patients reported improvements in physical (60%) and mental/behavioral symptoms (36%) following treatment. A minority of participants reported side effects, but they occurred in almost every body system and ranged in severity. Doctors relied on trial and error to determine treatment doses, frequency and components.Conclusions: MTHFR testing results in variable clinical processes in domains related to delivery of diagnosis and prognosis, and therapeutic options. However, patients report largely positive experiences. Clinicians and patients would benefit from therapeutic algorithms based on rigorous research.